2016
DOI: 10.1021/acs.chemrev.5b00465
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Biomaterials from Metabolically Derived Synthons

Abstract: The utility of metabolic synthons as the building blocks for new biomaterials is based on the early application and success of hydroxy acid based polyesters as degradable sutures and controlled drug delivery matrices. The sheer number of potential monomers derived from the metabolome (e.g., lactic acid, dihydroxyacetone, glycerol, fumarate) gives rise to almost limitless biomaterial structural possibilities, functionality, and performance characteristics, as well as opportunities for the synthesis of new polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 328 publications
0
46
0
Order By: Relevance
“…1,2 In an effort to expand the uses of APCs, researchers are currently focusing on the sustainable development of poly(carbonate)s through the synthesis of renewable monomers and polymers with degradable features. 3,4 From a biomedical point of view, poly(carbonate)s exhibit appealing degradation properties. Unlike poly(ester)s, APCs do not cause a local lowering of pH, which can be problematic for pH-sensitive drugs and the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In an effort to expand the uses of APCs, researchers are currently focusing on the sustainable development of poly(carbonate)s through the synthesis of renewable monomers and polymers with degradable features. 3,4 From a biomedical point of view, poly(carbonate)s exhibit appealing degradation properties. Unlike poly(ester)s, APCs do not cause a local lowering of pH, which can be problematic for pH-sensitive drugs and the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has worked with the synthesis of biomaterials using the biomolecule dihydroxyacetone (DHA, Figure ) . DHA is an attractive molecule for use in biodegradable biomaterials as it is a natural product in human metabolism and therefore offers reduced probability of toxicity and inflammation upon polymer degradation in the body . One intriguing characteristic of these materials is their unexpectedly rapid degradation rate under aqueous conditions .…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,15 ] Other examples of rapidly degradable hydrogel applications include template struc-in human metabolism and therefore offers reduced probability of toxicity and infl ammation upon polymer degradation in the body. [ 26 ] One intriguing characteristic of these materials is their unexpectedly rapid degradation rate under aqueous conditions. [27][28][29] Zawaneh et al reported 100% degradation of monomethoxy poly(ethylene glycol)-poly(DHA) diblock copolymers within 24 h, in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…DHA is a natural product in human, bacteria, and plants metabolism and plays an important role in the research of new biomaterials, biological polymers and drug designs. The low toxicity of DHA (LD 50 = 160000 mg · kg –1 ) proposes hopefully comparable properties for nitrated derivatives. Based on the fact, that sugars can react with primary amines to form brown pigments, DHA, a three‐carbon sugar, can also react with amino acids .…”
Section: Introductionmentioning
confidence: 99%